EXPERIENCE IN OPTIMIZING PHARMACOTHERAPY BASED ON CLINICAL OBSERVATIONS OF PATIENTS AFTER MYOCARDIAL INFARCTION WITH CHRONIC HEART FAILURE AND REDUCED AND MID-RANGE LEFT VENTRICULAR EJECTION FRACTION (International journal of medical sciences, 2026)
Chronic heart failure (CHF) remains one of the leading medical and social problems of modern cardiology, especially in patients who have experienced myocardial infarction. Despite the introduction of contemporary pharmacological treatment strategies, the prognosis of patients with CHF and reduced or mildly reduced left ventricular ejection fraction remains unfavorable, which is largely associated with neurohormonal activation and progressive myocardial remodeling. One of the key pathogenetic mechanisms in the development and progression of CHF is hyperactivation of the renin–angiotensin–aldosterone system, accompanied by excessive aldosterone production. In this regard, mineralocorticoid receptor antagonists occupy an important place in the basic quadruple therapy of CHF.Eplerenone, characterized by high selectivity for mineralocorticoid receptors, demonstrates pronounced cardioprotective properties, including reductions in mortality and hospitalization rates, attenuation of myocardial remodeling and fibrosis, and improvement in patients’ quality of life. The efficacy and safety of eplerenone have been confirmed in large randomized clinical trials such as EPHESUS, EMPHASIS-HF, and REMINDER.Thus, eplerenone is an essential component of modern CHF therapy, particularly in patients after myocardial infarction, contributing to improved prognosis and functional status.